Association of apolipoprotein E gene polymorphism with gallstone disease in Iraqi Kurdish women - SEERWAN Raheem; Ismail Salih Kakey (College of Pharmacy University of Baghdad, 2024)
Gallstone disease (GSD) is a worldwide problem; the frequency of GSD varies greatly amongst different ethnic groups, possibly due to environmental and genetic factors. One circulating lipoprotein involved in lipid metabolism is apolipoprotein E (APOE). The APOE gene is polymorphic, has three distinct alleles, APOE2, APOE3, and APOE4. The an APOE polymorphism is linked to a variety of diseases, including Alzheimer's and type-two diabetes, so this study aimed to assess the relationship among various APOE genotypes and alleles with gallstone cases in Iraqi Kurdish women. The present case-control study involved 81 cases with laparoscopic cholecystectomy for gallstone disease and 80 healthy women without GSD. Genomic DNA samples were taken from blood to find the genotype of APOE using allele-specific sequence-primers and a method based on polymerase chain reaction (PCR). lipid profiles were examined using an automated biochemical analyzer. SPSS and GraphPad Prism 9.1.1 software were used to conduct the statistical analysis. No significant relationships were found between healthy people and GSD patients in genotype and allele frequencies. However, the genotype for E3/E4 and the APOE4 allele in GSD patients were higher than the controls (9.88% vs. 5.0% and 4.94% vs. 2.5%, respectively; P <0.05) but statistically nonsignificant. serum levels of cholesterol, low-density lipoproteins, and very low-density lipoproteins were higher, and the levels of serum high-density lipoprotein was lower than controls. These findings revealed no connection between the examined polymorphisms and gallstone cases. Additionally, it was demonstrated that gallstone disease and lipid parameters had a favorable relationship. Keywords: Apolipoprotein E, APOE, Gallstone disease, Genotype, Polymorphisms.